Controlled trial of natamycin in the treatment of allergic bronchopulmonary aspergillosis. Issue 6 (June 1990) - Currie, D C; Lueck, C; Milburn, H J; Harvey, C; Longbottom, J L; Darbyshire, J H; Nunn, A J; Cole, P J
Abstract : Allergic bronchopulmonary aspergillosis often requires treatment with oral corticosteroids to control the host response to Aspergillus fumigatus. In a double blind study 25 patients with allergic bronchopulmonary aspergillosis taking maintenance oral corticosteroids were randomly allocated to receive 5 mg natamycin or placebo by nebuliser twice daily for one year. The primary aim of the study was to assess the steroid sparing potential of natamycin. Standardised reductions in corticosteroid dosage were therefore undertaken every five weeks, unless clinically contraindicated. Five patients were withdrawn in the first four months: two (1 natamycin, 1 placebo) died, two (1 natamycin, 1 placebo) had suspected drug reactions, and one (natamycin) was non-compliant. The pretreatment characteristics of the 20 patients (10 in each group) who completed the study were similar, 17 (9 natamycin, 8 placebo) having evidence of recent disease activity. At the end of the study prednisolone dose had been reduced by a similar amount in each group (median natamycin 2.25 mg, placebo 2.5 mg). Evidence of disease activity during the study year (transient shadowing on the chest radiograph, blood eosinophilia, or increases in antibodies to A fumigatus, or any combination of these) was observed in similar numbers of patients in each group (5 natamycin, 7 placebo). There was no evidence that natamycin conferred benefit on these patients with allergic bronchopulmonary aspergillosis.